2021
DOI: 10.18502/ijrm.v19i7.9472
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian reserve in women with endometriosis under total cystectomy compared to partial cystectomy: A randomized clinical trial

Abstract: Background: The standard procedure for ovarian endometriosis is laparoscopic excision of ovarian cysts and complete removal of the cyst capsule using the striping technique. Owing to the possibility of reducing ovarian reserve, and in some cases, the premature ovarian failure, the safety remains to be known. Objective: To compare the ovarian reserve in women with endometriosis who underwent total cystectomy with partial cystectomy. Materials and Methods: In this randomized clinical trial, 56 women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The effect of surgery for ovarian endometriosis on markers of ovarian reserve has been previously discussed in this article. The results of those studies [17][18][19][20][21][22]24] reinforce the ESHRE recommendation to avoid surgery for ovarian endometrioma unless required to improve endometriosis-associated pain or accessibility of follicles [2]. A study looking at the surgical treatment of endometrioma >3 cm prior to IVF found a similar CPR and LBR as in women with unexplained infertility, however this was a prospective case-control study despite identifying itself as an RCT [40].…”
Section: Surgery Prior To Medically Assisted Reproduction In Women Wi...mentioning
confidence: 82%
See 1 more Smart Citation
“…The effect of surgery for ovarian endometriosis on markers of ovarian reserve has been previously discussed in this article. The results of those studies [17][18][19][20][21][22]24] reinforce the ESHRE recommendation to avoid surgery for ovarian endometrioma unless required to improve endometriosis-associated pain or accessibility of follicles [2]. A study looking at the surgical treatment of endometrioma >3 cm prior to IVF found a similar CPR and LBR as in women with unexplained infertility, however this was a prospective case-control study despite identifying itself as an RCT [40].…”
Section: Surgery Prior To Medically Assisted Reproduction In Women Wi...mentioning
confidence: 82%
“…Many studies evaluated these surrogate markers and consistently found a reduction in AFC [17,18] and AMH [17,[19][20][21], and an increase in FSH [17]. Bilateral endometrioma surgery had a greater effect on these surrogate markers than unilateral [19] and total cystectomy reduced AMH more than partial cystectomy [22].…”
Section: Ovarian Endometriosismentioning
confidence: 99%